Antidepressant-like effects and memory enhancement of a herbal formula in mice exposed to chronic mild stress - Xiu-Ping Sun; Si-Di Li; Zhe Shi; Teng-Fei Li; Rui-Le Pan; Qi Chang; Chuan Qin; Xin-Min Liu (Neuroscience Bulletin, 2013)

Effects of the Conversion of Native Vegetation to Farmlands on Soil Microarthropod Biodiversity and Ecosystem Functioning in a Desert Oasis - Feng-Rui Li; Qi Feng; Ji-Liang Liu; Te-Sheng Sun; Wei Ren; Zhen-Huan Guan (Ecosystems, 2013)

Screening of Actinobacillus pleuropneumoniae LuxS Inhibitors - Lu Li; Lili Sun; Yunfeng Song; Xinjuan Wu; Xuan Zhou; Ziduo Liu; Rui Zhou (Current Microbiology, 2013)

Effect of sulphate nutrition on arsenic translocation and photosynthesis of rice seedlings - Rui Song; Chen-Yun Zhao; Juan Liu; Jing Zhang; Yan-Xiu Du; Jun-Zhou Li; Hong-Zheng Sun; Hong-Bing Zhao; Quan-Zhi Zhao (Acta Physiologiae Plantarum, 2013)

Transcriptome profiling and digital gene expression analysis of Nile tilapia (Oreochromis niloticus) infected by Streptococcus agalactiae - Rui Zhang; Li-li Zhang; Xing Ye; Yuan-yuan Tian; Cheng-fei Sun; Mai-xin Lu; Jun-jie Bai (Molecular Biology Reports, 2013)

Regulation of phenylalanine ammonia-lyase (PAL) gene family in wood forming tissue of Populus trichocarpa - Rui Shi; Christopher M. Shuford; Jack P. Wang; Ying-Hsuan Sun; Zhichang Yang; Hsi-Chuan Chen; Sermsawat Tunlaya-Anukit; Quanzi Li; Jie Liu; David C. Muddiman; Ronald R. Sederoff; Vincent L. Chiang (Planta, 2013)

Arm–eye coordination test to objectively quantify motor performance and muscles activation in persons after stroke undergoing robot-aided rehabilitation training: a pilot study - Rong Song; Kai-Yu Tong; Xiaoling Hu; Le Li; Rui Sun (Experimental Brain Research, 2013)

In vitro mutagenesis and directed screening for salt-tolerant mutants in peanut - Ming-Xia Zhao; Hai-Yan Sun; Rui-Rui Ji; Xiao-Hui Hu; Jiong-Ming Sui; Li-Xian Qiao; Jing Chen; Jing-Shan Wang (Euphytica, 2013)

Clinical and angiographic features associated with coronary collateralization in stable angina patients with chronic total occlusion - Zhen Sun; Ying Shen; Lin Lu; Rui-yan Zhang; Li-jin Pu; Qi Zhang; Zheng-kun Yang; Jian Hu; Qiu-jing Chen; Wei-feng Shen (Journal of Zhejiang University-SCIENCE B, 2013)

The member of high temperature requirement family HtrA2 participates in neuronal apoptosis after intracerebral hemorrhage in adult rats - Huiqing Sun; Lei Li; Feng Zhou; Lin Zhu; Kaifu Ke; Xiang Tan; Wei Xu; Ying Rui; Heyi Zheng; Zhengming Zhou; Huiguang Yang (Journal of Molecular Histology, 2013)

Meso-Cenozoic extensional structures in the Northern Tarim Basin, NW China - Yue-Jun Li; Yan Zhao; Long-De Sun; Wen-Jie Song; Duo-Ming Zheng; Ya-Lei Liu; Dao-Xuan Wang; Jian-Feng Hu; Qi-Rui Zhang (International Journal of Earth Sciences, 2013)

A miR-570 binding site polymorphism in the B7-H1 gene is associated with the risk of gastric adenocarcinoma - Weipeng Wang; Fang Li; Yong Mao; Huan Zhou; Jing Sun; Rui Li; Cuiping Liu; Weichang Chen; Dong Hua; Xueguang Zhang (Human Genetics, 2013)

MicroRNAs-1614-3p gene seed region polymorphisms and association analysis with chicken production traits - Hong Li; Gui-Rong Sun; Ya-Dong Tian; Rui-Li Han; Guo-Xi Li; Xiang-Tao Kang (Journal of Applied Genetics, 2013)

Pelagibacterium nitratireducens sp.nov., A Marine Alphaproteobacterium Isolated from the East China Sea - Qipei Li; Yongle Xu; Keshao Liu; Lanlan Cai; Yingnan Fu; Jia Sun; Rui Zhang (Current Microbiology, 2013)

Comparison of transcriptome under red and blue light culture of Saccharina japonica (Phaeophyceae) - Wen-Jun Wang; Fei-Jiu Wang; Xiu-Tao Sun; Fu-Li Liu; Zhou-Rui Liang (Planta, 2013)

Inhibition of autophagy enhances anticancer effects of bevacizumab in hepatocarcinoma - Xian-ling Guo; Ding Li; Kai Sun; Jin Wang; Yan Liu; Jian-rui Song; Qiu-dong Zhao; Shan-shan Zhang; Wei-jie Deng; Xue Zhao; Meng-chao Wu; Li-xin Wei (Journal of Molecular Medicine, 2013)

Overexpression of integrin-linked kinase (ILK) is associated with tumor progression and an unfavorable prognosis in patients with colorectal cancer - Rui Li; Baolin Liu; Hongzhuan Yin; Wei Sun; Jianqiao Yin; Qi Su (Journal of Molecular Histology, 2013)

Antidepressant-like effect of flaxseed secoisolariciresinol diglycoside in ovariectomized mice subjected to unpredictable chronic stress - Xing Ma; Rui Wang; Xin Zhao; Chong Zhang; Jiao Sun; Jianxin Li; Lu Zhang; Tuo Shao; Lina Ruan; Liang Chen; Ying Xu; Jianchun Pan (Metabolic Brain Disease, 2013)

Spatial patterns and climate drivers of carbon fluxes in terrestrial ecosystems of China - Gui‐Rui Yu; Xian‐Jin Zhu; Yu‐Ling Fu; Hong‐Lin He; Qiu‐Feng Wang; Xue‐Fa Wen; Xuan‐Ran Li; Lei‐Ming Zhang; Li Zhang; Wen Su; Sheng‐Gong Li; Xiao‐Min Sun; et al. (Global Change Biology, 2013)
Understanding the dynamics and underlying mechanism of carbon exchange between terrestrial ecosystems and the atmosphere is one of the key issues in global change research. In this study, we quantified the carbon fluxes in different terrestrial ecosystems in China, and analyzed their spatial variation and environmental drivers based on the long‐term observation data of China FLUX sites and the published data from other flux sites in China. The results indicate that gross ecosystem productivity ( GEP ), ecosystem respiration ( ER ), and net ecosystem productivity ( NEP ) of terrestrial ecosystems in China showed a significantly latitudinal pattern, declining linearly with the increase of latitude. However, GEP , ER , and NEP did not present a clear longitudinal pattern. The carbon sink functional areas of terrestrial ecosystems in China were mainly located in the subtropical and temperate forests, coastal wetlands in eastern China, the temperate meadow steppe in the northeast China, and the alpine meadow in eastern edge of Qinghai‐Tibetan Plateau. The forest ecosystems had stronger carbon sink than grassland ecosystems. The spatial patterns of GEP and ER in China were mainly determined by mean annual precipitation ( MAP ) and mean annual temperature ( MAT ), whereas the spatial variation in NEP was largely explained by MAT . The combined effects of MAT and MAP explained 79%, 62%, and 66% of the spatial variations in GEP , ER , and NEP , respectively. The GEP , ER , and NEP in different ecosystems in China exhibited ‘positive coupling correlation’ in their spatial patterns. Both ER and NEP were significantly correlated with GEP , with 68% of the per‐unit GEP contributed to ER and 29% to NEP . MAT and MAP affected the spatial patterns of ER and NEP mainly by their direct effects on the spatial pattern of GEP .

Spatio-temporal reconstruction of air temperature maps and their application to estimate rice growing season heat accumulation using multi-temporal MODIS data - Li-wen Zhang; Jing-feng Huang; Rui-fang Guo; Xin-xing Li; Wen-bo Sun; Xiu-zhen Wang (Journal of Zhejiang University-SCIENCE B, 2013)

A stepwise cloud shadow detection approach combining geometry determination and SVM classification for MODIS data - Rui Zhang; Donglian Sun; Sanmei Li; Yunyue Yu (International Journal of Remote Sensing, 2013)